Sosialisasi Dan Pelatihan Digital Marketing Sebagai Sarana Media Promosi UMKM Pada Kelurahan Purwosari Kecamatan Mijen Kota Semarang - Deewar Mahesa; Jaluanto Sunu Punjul Tyoso; Puji Setya Sunarka (Universitas Maritim AMNI Semarang, 2024)
The Covid-19 pandemic has driven major changes in business, with an increase in online activities such as working, studying and shopping. MSME players must adapt to this condition, utilizing digital marketing to market their products. The service team held outreach and training to increase MSMEs' understanding of the benefits of digital marketing, encouraging the use of social media in marketing. Observation, socialization and training methods are expected to increase participants' knowledge in using online media as a marketing tool, open wider market opportunities and increase business income. This activity aims to increase the digital literacy of MSMEs, overcome digital technology obstacles, and strengthen product marketing through digital marketing.